2017
DOI: 10.5468/ogs.2017.60.6.542
|View full text |Cite|
|
Sign up to set email alerts
|

The clinical significance of D-dimer concentrations in patients with gestational hypertensive disorders according to the severity

Abstract: ObjectivePregnancy is a major risk factor of thromboembolism, and the patients with preeclampsia (PE) are known to have higher risk of thromboembolic complications than normal pregnant women. D-dimer is a well-established laboratory marker for the screening of venous thromboembolism (VTE), but the concentrations of d-dimer tend to increase physiologically in pregnant women throughout the gestational age. We performed this study to evaluate the clinical significance of d-dimer concentrations in patients with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…2), with a high positive predictive value of 94.4% and a positive likelihood ratio of 8.5. Dusse et al 19 and Kim et al 21 found a significant elevation of D-dimer in patients with severe pre-eclampsia versus patients without criteria for severity. Similarly, the present study found a significant association between elevated D-dimer levels (>97.5 percentile for gestational age) and patients with criteria of severity (19.3% vs 2.3%.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…2), with a high positive predictive value of 94.4% and a positive likelihood ratio of 8.5. Dusse et al 19 and Kim et al 21 found a significant elevation of D-dimer in patients with severe pre-eclampsia versus patients without criteria for severity. Similarly, the present study found a significant association between elevated D-dimer levels (>97.5 percentile for gestational age) and patients with criteria of severity (19.3% vs 2.3%.…”
Section: Resultsmentioning
confidence: 97%
“…It has also been confirmed that D-dimer is significantly elevated in pregnant patients who have severe pre-eclampsia versus normotensive patients or those with mild pre-eclampsia. 19,21 Moreover, Pinheiro et al 1 found that D-dimer is an excellent predictor of the severity of pre-eclampsia, with an area under the receiver operating characteristic (ROC) curve of 90%.…”
Section: Introductionmentioning
confidence: 99%
“…Our results agreed with the recent study by Kim et al in 2017, which investigated the clinical importance of D-dimer amounts in GH patients according to the severity of the disease. They stated that 80% of patients with GH who enrolled in their study had substantial elevations in the concentration of D-dimer (19). They also uncovered that the average of D-dimer concentration was notably greater in patients with severe GH than in those with nonsevere GH (19).…”
Section: Figure 3 the Correlation Of D-dimer Levels With Gestationalmentioning
confidence: 97%
“…They stated that 80% of patients with GH who enrolled in their study had substantial elevations in the concentration of D-dimer (19). They also uncovered that the average of D-dimer concentration was notably greater in patients with severe GH than in those with nonsevere GH (19). Nevertheless, due to the variances in the averages of D-dimer concentrations among females with severe GH and non-severe GH, D-dimer cannot be used as an indicator or screening tool for identifying severe GH.…”
Section: Figure 3 the Correlation Of D-dimer Levels With Gestationalmentioning
confidence: 99%
See 1 more Smart Citation